THE INFLUENCE OF USING WH-QUESTION AS TEACHING GUIDANCE TOWARD THE STUDENTS’ ABILITY IN WRITING RECOUNT-TEXT - Sujarwati, Iis (English Education: Jurnal Tadris Bahasa Inggris, 2013)
The objectives of this research were (1) to know about the students’ ability inwriting recount text after being taught without using wh-question as teaching guidance,(2) To know the students’ ability in writing recount text after being taught by using Whquestion as teaching guidance, and (3) To know whether there is a significantimprovement of the students’ ability in writing recount text who taught by using whquestion.The hypothesis of the research are (1) There is no significant improvement of thestudents’ ability in writing recount text who taught by using wh-question (H0) and (2)There is a significant improvement of the students’ ability in writing recount text whotaught by using wh-question (H1).This research is using an experimental design and quantitative method. Incollecting the data, the researcher used pre-test and post-test. The hypothesis was testedby using t-test.The research findings have shown the result of control class which is theiraverage score at pre-test is 55, 51. Then, their score at post test is 60, 89. Meanwhile, theresult of experimental class showed an improvement score from 55, 7 at pre-test andbecame 69, 28 at post-test.By seeing the result of hypothesis testing, it is gained that at the significant levelof 0.05 (5%) t-ratio (4.09) is higher than t-table (2.00) or 4.09 > 2.00, so that H0 is rejectedand H1 is accepted. Therefore, the hypothesis of this research is proved.